1992
DOI: 10.1095/biolreprod47.5.889
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Immunocytochemical Localization of an Estrogen-Dependent Glycoprotein and Associated Morphological Alterations in the Sheep Ampulla Oviduct1

Abstract: Published reports have shown that an M(r) 90,000-92,000 protein is released into the oviductal lumen of the sheep, during estrus at a time corresponding to ovulation and fertilization, where it associates with the embryo. The objectives of this study were (a) to determine whether estradiol-17 beta (E) alone or in combination with progesterone (P) induces the synthesis of the M(r) 90,000-92,000 protein from the ampulla and/or isthmus oviduct; (b) to monitor structural alterations in oviductal epithelial cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
80
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 0 publications
16
80
1
Order By: Relevance
“…Firstly, as described above, the number of viable embryos was related to the oestradiol concentrations around oestrus, but oestradiol is not only the signal of a healthy population of preovulatory follicles. Oestradiol induces maturation and differentiation of the secretory apparatus of the epithelial cells of the sheep ampulla oviduct [30]. In response to the oestradiol levels around the oestrus [31], these cells synthesize and secrete a specific oestrus-associated glycoprotein (oEGP) which regulates embryo development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, as described above, the number of viable embryos was related to the oestradiol concentrations around oestrus, but oestradiol is not only the signal of a healthy population of preovulatory follicles. Oestradiol induces maturation and differentiation of the secretory apparatus of the epithelial cells of the sheep ampulla oviduct [30]. In response to the oestradiol levels around the oestrus [31], these cells synthesize and secrete a specific oestrus-associated glycoprotein (oEGP) which regulates embryo development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the GAGs in the fluid secreted by the genital organs of bitches may serve to accelerate the capacitation of dog sperm. The secretory function of oviductal epithelial cells has been found to become active in the estrous period of different species [1,18,27], and non-ciliated cells in the ampulla of the oviduct have been observed to secrete large amounts of glycoproteins in estrous ewes [27] and mice [26]. Furthermore, it has been reported that the oviductal fluid of estrous cows contains a large volume of GAGs [2,8,17], and GAGs have been detected not only in the oviductal fluid of the cow [17] and ewe [18] but in their uterine fluid as well.…”
Section: Discussionmentioning
confidence: 99%
“…The differences are difficult to explain, since even within the primate species variations in sensitivity to fluctuations estradiol and progesterone have been seen. The presence of ciliated cells in the isthmus, ampulla (Murray, 1992(Murray, , 1995 and fimbria Murray, 1996) oviducts of long-term ovariectomized ewes indicates that the sheep lacks a steroid-dependent ciliation-deciliation process which characterizes the oviducts of human (Verhage et al, 1979) and nonhuman primates (Rumery et al, 1978;Brenner and Slayden, 1994;Verhage et al, 1990), cats (Verhage and Brenner, 1975) and dogs (Verhage et al., 1973). In the sheep, this could account for the lack of significant changes as estradiol levels fall and progesterone levels rise at day 3 of pregnancy (Bazer and First, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Using biochemical and molecular analyses, we have shown that the isthmus oviduct of the sheep does not express or synthesize the Mr 90,000-116,000 protein (Murray, 1992(Murray, , 1993DeSouza and Murray, 1995). Immunocytochemistry and in situ hybridization have failed to detect the Mr 90,000-116,000 protein or its mRNA, respectively, in tissue sections of the estrogen-dominated isthmus epithelium (Murray, 1992;Murray and DeSouza, 1995). The data presented here provide additional cytological evidence for the lack of cellular stores of the estrogendependent oviduct glycoprotein in ciliated or nonciliated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation